1994
DOI: 10.1042/bj3040869
|View full text |Cite
|
Sign up to set email alerts
|

γ-Glutamyltranspeptidase-catalysed acyl-transfer to the added acceptor does not proceed via the ping-pong mechanism

Abstract: Acyl-transfer catalysed by gamma-glutamyltranspeptidase from bovine kidney was studied using gamma-L- and gamma-D-Glu-p-nitroanilide as the donor and GlyGly as the acceptor. The transfer of the gamma-Glu group to GlyGly was shown to be accompanied by transfer of the gamma-Glu group to water (hydrolysis). The results were compared with acyl-transfer catalysed by the representative serine protease, alpha-chymotrypsin. The main difference between the kinetic mechanism of the acyl-transfer reactions catalysed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…1 Abbreviations: CHES, 2-[N-cyclohexylamino]ethane sulfonic acid; DON, 6-diazo-5-oxo-L-norleucine; GGT, γ-glutamyl transpeptidase (EC 2.3.2.2); GSH, glutathione (γ-Glu-Cys-Gly); kie, kinetic isotope effect; MOPS, 3-[N-morpholino]propane sulfonic acid; Tris, tris(hydroxymethyl)aminomethane. the mechanistic pathway is sequential, with random addition of substrates and ordered release of products (15). Currently, the amino acid residues involved in the enzymatic catalysis of rat kidney GGT, including the active site nucleophile, have not been identified.…”
mentioning
confidence: 99%
“…1 Abbreviations: CHES, 2-[N-cyclohexylamino]ethane sulfonic acid; DON, 6-diazo-5-oxo-L-norleucine; GGT, γ-glutamyl transpeptidase (EC 2.3.2.2); GSH, glutathione (γ-Glu-Cys-Gly); kie, kinetic isotope effect; MOPS, 3-[N-morpholino]propane sulfonic acid; Tris, tris(hydroxymethyl)aminomethane. the mechanistic pathway is sequential, with random addition of substrates and ordered release of products (15). Currently, the amino acid residues involved in the enzymatic catalysis of rat kidney GGT, including the active site nucleophile, have not been identified.…”
mentioning
confidence: 99%
“…The present modification experiments showed that the inactivation of the present GGT by DFP could be fully reversed by the addition of 2-ME, indicating that a cysteinyl residue and not a seryl residue was affected by DFP. The rat kidney GGT contains Thr-523, another hydroxy amino acid, which interacts with the substrate analog acivicin (8,45). Provided that more detailed studies of the present GGT support these preliminary observations, the treponemal GGT may turn out to be catalytically and structurally relatively similar to mammalian GGTs studied previously and to differ from the E. coli GGT with regard to association with a carbohydrate moiety.…”
Section: Discussionmentioning
confidence: 99%